Synthesis and investigation of the conversion reactions of pyrimidine-thiones with nucleophilic reagent and evaluation of their acetylcholinesterase, carbonic anhydrase inhibition, and antioxidant activities - Parham, Taslimi; Afsun, Sujayev; Fikret, Turkan; Emin, Garibov; Zubeyir, Huyut; Vagif, Farzaliyev; Sevgi, Mamedova; Gülçin, İlhami (Wiley, 2018)
The conversion reactions of pyrimidine-thiones with nucleophilic reagent were studied during this scientific research. For this purpose, new compounds were synthesized by the interaction between 1,2-epoxy propane, 1,2-epoxy butane, and 4-chlor-1-butanol and pyrimidine-thiones. These pyrimidine-thiones derivatives (A-K) showed good inhibitory action against acetylcholinesterase (AChE), and human carbonic anhydrase (hCA) isoforms I and II. AChE inhibition was in the range of 93.1 +/- 33.7-467.5 +/- 126.9nM. The hCA I and II were effectively inhibited by these compounds, with K-i values in the range of 4.3 +/- 1.1-9.1 +/- 2.7nM for hCA I and 4.2 +/- 1.1-14.1 +/- 4.4nM for hCA II. On the other hand, acetazolamide clinically used as CA inhibitor showed K-i value of 13.9 +/- 5.1nM against hCA I and 18.1 +/- 8.5nM against hCA II. The antioxidant activity of the pyrimidine-thiones derivatives (A-K) was investigated by using different in vitro antioxidant assays, including Cu(2+)and Fe(3+)reducing, 1,1-diphenyl-2-picrylhydrazyl (DPPH center dot) radical scavenging, and Fe(2+)chelating activities.
Keywords: Acetylcholinesterase; Antioxidant activity; Carbonic anhydrase; Enzyme inhibition; Pyrimidine-thiones